Analysis of Fair Play Violations in Badminton Matches (Case Study: Sirnas B Kepulauan Riau 2025) - FATIMATUS MUKAROMAH; Nazwa Luthfia Septiani; Nur Khasanah Siregar (Indonesian Journal of Sports Law, 2025)
This study aims to analyze violations of the principle of fair play in badminton matches at the 2025 Sirnas B Kepulauan Riau tournament. The cases discussed involve unsportsmanlike conduct that occurred during the matches. The method used is normative legal research with a regulatory and case study approach. The results of the study indicate that such actions are inconsistent with the principle of fair play and also violate the rules applicable in badminton. This behavior not only harms opponents but also undermines the values of fairness in sports. Therefore, stricter enforcement of the rules is necessary to ensure that matches remain fair and sportsmanlike.